Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata (KKN) di MTs Yayasan Al-Barkah – Curug - Uswatun Khasanah; Myda Lanniati; Julianto; Namira Kafka Maulidya; Asri Wulan Fadillah Sari; Fatya Nisa Salsabila; Salma Mayviana Zahrani; Fitri Nurlaila; Shafira Azhar; Fatimah Azzahro (Masyarakat Ekonomi Syariah Bogor, 2025)
Real Work Lectures (KKN) are community service activities that are expected to be part of empowerment and learning for students to see the true social reality of society. In this activity, students are required to interact and try to solve various problems that exist in society and look for potentials that can be explored or utilized so that it can become a sustainable activity. Real Work Lectures (KKN) are a forum for students to apply the knowledge gained from higher education in society. It is hoped that the implementation of KKN as a vehicle for community service can also develop students' practical abilities in absorbing skills that exist in society. So it is hoped that KKN will be able to help solve problems in society by optimizing existing resources. Real Work Lectures (KKN), which were born from the development process, are essentially the implementation of the national education philosophy, within the framework of the Tri Darma of Higher Education. One application of community service is manifested in Real Work Lectures (KKN) which will be held at the Mts Al-Barkah – Curug Foundation.